Silicon and Plants (Advancements in Homeopathic Research, 2022)
Silicon is the second most abundant element in the earth’s crust. The average concentration of Si in the lithosphere is about 28 per cent and in soils normally ranges between 23-35 per cent. It is a principal soil component lost during weathering and the conversions of silicon to secondary minerals are most important mechanisms of soil formation.1silicon is needed at certain stages of plant growth, including biosilicification of grass leaves and during grain development in rice. The plants use silicon to enhance their physical strength. However, silicon is also required for other physiological processes, as well. Silicon helps plants deal with stress and is needed prior to or at the time of a stress event to impart its beneficial effects.2
Keywords: Silicon; soil; uptake; distribution; functions; stress relief